2002
DOI: 10.1095/biolreprod.101.000976
|View full text |Cite
|
Sign up to set email alerts
|

Src Tyrosine Kinase-Induced Loss of Luteinizing Hormone Responsiveness Is via a Ras-Dependent, Phosphatidylinositol-3-Kinase Independent Pathway1

Abstract: Gonadotropins stimulate gonadal cell steroid secretion primarily through activation of a cAMP-protein kinase A signal transduction pathway. Various growth factors have been shown to inhibit gonadotropin-stimulated steroidogenesis, however, the intracellular signaling cascades involved in growth factor inhibition have not been characterized. The present study investigated whether Src tyrosine kinase, a nonreceptor tyrosine kinase activated in response to growth factor stimulation and previously shown to inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Cellular stress leading to the activation of the p38 MAP kinase also induces PKB activation, indicating a multiplicity of signaling pathways that activate PKB. However, Taylor (2002) failed to show an involvement of PI3K in the hormone‐induced steroid formation by MA‐10 cells. In preliminary studies, we also failed to show a role of PKB in Leydig cell steroidogenesis after silencing the PKB mRNA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular stress leading to the activation of the p38 MAP kinase also induces PKB activation, indicating a multiplicity of signaling pathways that activate PKB. However, Taylor (2002) failed to show an involvement of PI3K in the hormone‐induced steroid formation by MA‐10 cells. In preliminary studies, we also failed to show a role of PKB in Leydig cell steroidogenesis after silencing the PKB mRNA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK cascade may involve other signaling molecules such as SFKs, β-arrestins, PKA, Ras, Shc and the EGFR as intermediates in the pathway [64-69]. Studies carried out employing inhibitors and dominant negative constructs of SFKs have shown that many of these molecules interact with the canonical LH/CGR activated signaling pathway resulting in altered responsiveness to steroidogenesis in ovarian cells [19,70,71], MA-10 tumor Leydig cells [18,72,73] and adrenal cells [74,75]. In the present study, expression of genes belonging to SFKs confirm low levels of activated Src during high steroidogenic state or increased activated levels of Src during low steroidogenic state of the CL.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the LH/CGR and SFKs can possibly either be a direct [17,76] or indirect involving Pyk2 [77] or β-arrestins [66,78] to keep Src activation in check. Thus, increased Src activation observed during low P 4 secretion may be due to reduced responsiveness to LH since cAMP-PDE activity involving Ras activation may be affected as observed in MA-10 and ovarian theca cells [18,19,73]. The role of PDE in the regulation of endocrine cell functions has been well documented [79-83].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies demonstrated that stimulation of Src activity resulted in reduced steroidogenesis. In porcine thecal cells PDGF-mediated stimulation of Src activity resulted in reduced gonadotropin-stimulated steroidogenesis [36]. In addition, transfection of MA10 and TM3 Leydig cell lines with a temperature sensitive constitutively active Src mutant also resulted in inhibition of cAMP-stimulated steroidogenesis [6, 8].…”
Section: Discussionmentioning
confidence: 99%